Stomal Closure: Strategies to Prevent Incisional Hernia - Harries, Rhiannon L.; Torkington, Jared (Frontiers in Surgery, 2018)
Incisional hernias following ostomy reversal occur frequently. Incisional hernias at the site of a previous stoma closure can cause significant morbidity, impaired quality of life, lead to life-threatening hernia incarceration or strangulation and result in a significant financial burden on health care systems Despite this, the evidence base on the subject is limited. Many recognised risk factors for the development of incisional hernia following ostomy reversal are related to patient factors such as age, malignancy, diabetes, COPD, hypertension and obesity, and are not easily correctable. There is a limited amount of evidence to suggest that prophylactic mesh reinforcement may be of benefit to reduce the post stoma closure incisional hernia rate but a further large scale randomised controlled trial is due to report in the near future. There appears to be weak evidence to suggest that surgeons should favour circular, or ‘purse-string’ closure of the skin following stoma closure in order to reduce the risk of SSI, which in turn may reduce incisional hernia formation. There remains the need for further evidence in relation to suture technique, skin closure techniques, mechanical bowel preparation and oral antibiotic prescription focusing on incisional hernia development as an outcome measure. Within this review, we discuss in detail the evidence base for the risk factors for the development of, and the strategies to prevent ostomy reversal site incisional hernias.